Dampak Penggunaan Media Interaktif terhadap Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan - M. Ichsan; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2023)
This research aims to determine the impact of using the interactive media Quizizz on student learning outcomes in the subject of Basic Electrical Engineering for the 10th-grade students at SMK Negeri 1 Lintau. Interactive learning media has not been fully utilized in the teaching of Basic Electrical Engineering. The rapid development of gadgets and technology has led students to frequently engage with gadgets during the learning process, often without using them for educational purposes, affecting their cognitive development. Therefore, this research was conducted to assess the impact of using interactive media on student learning outcomes. This research employed an experimental approach, a pre-experimental design with a one-group pretest-posttest design. The subjects of the study were the 10th-grade students from TK 2 at SMK Negeri 1 Lintau Buo for the academic year 2022/2023, comprising 30 students. To measure the effectiveness of the research, a pretest was administered before the use of Quizizz media in the teaching of Basic Electrical Engineering. A post-test was given after the instructional process using Quizizz media to teach Basic Electrical Engineering. The results of the research were analyzed using classical mastery testing, learning outcome improvement, and effect size testing. The test results showed that students who were exposed to Quizizz media performed better compared to those who were not exposed to Quizizz media. The learning outcomes of students improved after using Quizizz media, indicating the effectiveness of Quizizz media in enhancing student learning outcomes.